Ovine RAP1GAP and rBAT gene polymorphisms and their association with tail fat deposition in Hu sheep - Ma, Zongwu; Wang, Weimin; Zhang, Deyin; Zhang, Yukun; Zhao, Yuan; Li, Xiaolong; Zhao, Liming; Lin, Changchun; Wang, Jianghui; Zhou, Bubo; Cheng, Jiangbo; Xu, Dan; et al. (Frontiers in Veterinary Science, 2022)
Excessive fat deposition in the tail of sheep will affect its feed efficiency, which will increase the feeding cost. The purpose of this study was to identify the single nucleotide polymorphisms (SNPs) of RAP1GAP and rBAT genes by PCR amplification and Sanger sequencing, the SNPs were genotyped by KASP genotyping assays to evaluate their association with tail fat deposition traits. The results showed that two intronic mutations of g.13561 G > A and g.1460 T > C were found in RAP1GAP and rBAT, respectively. There were three genotypes of GG, AG, AA and CC, CT and TT at these two loci, respectively. Association analysis showed that g.13561 G > A of RAP1GAP was associated with tail width, tail fat weight and relative tail fat weight (P < 0.05). The g.1460 T > C of rBAT was associated with tail width and tail fat weight (P < 0.05). Different combinations of genotypes also differed significantly with tail fat deposition traits. In the tail fat tissue, the expression levels of RAP1GAP gene was significantly higher in small-tailed sheep than in big-tailed sheep, and the expression levels of rBAT gene was significantly higher in big-tailed sheep than in small-tailed sheep. In the liver, the expression levels of RAP1GAP and rBAT gene was significantly higher at 6 months than at 0 and 3 months. In conclusion, RAP1GAP and rBAT polymorphisms can be used as a candidate molecular marker to reduce tail fat deposition in sheep.